Double Header: Peter Boyko for MCPS SMOB - Treviño, Lorena; Boyko, Peter (I Hate Politics Podcast, 2025)
Guest Host Lorena Treviño of Walter Johnson High School talks with NorthwestHigh School junior Peter Boyko, one of two finalists for the Student Member of the Montgomery County Board of Education in 2025-26. The SMOB is one of eight on the county school board, nearly co-equal with other generally elected members, but voted in by MCPS secondary school students only. Music for this episode comes from Adam Bobrow. Suvarna Insta: @peterforsmob.
Keywords: I Hate Politics